Wnt‐induced deubiquitination FoxM1 ensures nucleus β‐catenin transactivation. (24th February 2016) - Chen, Yaohui; Li, Yu; Xue, Jianfei; Gong, Aihua; Yu, Guanzhen; Zhou, Aidong; Lin, Kangyu; Zhang, Sicong; Zhang, Nu; Gottardi, Cara J; Huang, Suyun
Abstract: A key step of Wnt signaling activation is the recruitment of β‐catenin to the Wnt target‐gene promoter in the nucleus, but its mechanisms are largely unknown. Here, we identified FoxM1 as a novel target of Wnt signaling, which is essential for β‐catenin/TCF4 transactivation. GSK3 phosphorylates FoxM1 on serine 474 which induces FoxM1 ubiquitination mediated by FBXW7. Wnt signaling activation inhibits FoxM1 phosphorylation by GSK3–Axin complex and leads to interaction between FoxM1 and deubiquitinating enzyme USP5, thereby deubiquitination and stabilization of FoxM1. FoxM1 accumulation in the nucleus promotes recruitment of β‐catenin to Wnt target‐gene promoter and activates the Wnt signaling pathway by protecting the β‐catenin/TCF4 complex from ICAT inhibition. Subsequently, the USP5–FoxM1 axis abolishes the inhibitory effect of ICAT and is required for Wnt‐mediated tumor cell proliferation. Therefore, Wnt‐induced deubiquitination of FoxM1 represents a novel and critical mechanism for controlling canonical Wnt signaling and cell proliferation. Synopsis: Wnt signaling stabilizes FoxM1, suppressing its phosphorylation by GSK3 and promoting its interaction with USP5. FoxM1 in turn interacts with beta‐catenin and abolishes the inhibitory effect of ICAT, leading to Wnt target‐gene expression and tumor cell proliferation. Wnts inhibit phosphorylation of FoxM1 by GSK3 to protect it from FBXW7‐mediated ubiquitination‐dependent degradation. Wnts induce the interaction between FoxM1 and the deubiquitinase USP5, leading to stabilization of FoxM1. Nuclear FoxM1/beta‐catenin interaction controls Wnt target‐gene expression by abolishing ICAT's inhibition. Abstract : Wnt signaling stabilizes FoxM1, suppressing its phosphorylation by GSK3 and promoting its interaction with USP5. FoxM1 in turn interacts with beta‐catenin and abolishes the inhibitory effect of ICAT, leading to Wnt target‐gene expression and tumor cell proliferation.